2023
DOI: 10.3390/en16083484
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Mineral and Rock Wettability Changes Induced by Reaction: Implications for CO2 Storage in Saline Reservoirs

Abstract: Wettability in CO2-brine-mineral/rock systems is an important parameter influencing CO2 storage capacities and leakage risks in saline reservoirs. However, CO2 tends to react with various minerals and rocks at subsurface conditions, thus causing temporal and spatial wettability changes. Although many relevant research works have been published during past years, a thorough overview of this area is still lacking. Therefore herein, reaction-induced wettability changes are reviewed, and the underlying mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…But extracting residual oil from tight reservoirs in complex geological formations remains a significant challenge [1]. Numerous studies have demonstrated the significant impact of CO 2 flooding on enhancing oil recovery (EOR) in low-permeability reservoirs [2][3][4][5]. CO 2 flooding holds the potential for achieving high efficiency in extracting oil from reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…But extracting residual oil from tight reservoirs in complex geological formations remains a significant challenge [1]. Numerous studies have demonstrated the significant impact of CO 2 flooding on enhancing oil recovery (EOR) in low-permeability reservoirs [2][3][4][5]. CO 2 flooding holds the potential for achieving high efficiency in extracting oil from reservoirs.…”
Section: Introductionmentioning
confidence: 99%